2020
DOI: 10.1177/0886260520967755
|View full text |Cite
|
Sign up to set email alerts
|

Examining Factors Associated with Stalking-Related Fears Among Men and Women Stalked by Male and Female Acquaintances

Abstract: This study examines experiences of acquaintance stalking victims ( n = 389), recruited from a community sample, by victim and stalker gender and explores factors associated with three measures of fear (fear of harm, perceived capability of stalker to harm, and fear of significant life impact). There were five main findings from this study: (a) although research suggests ex-partner stalkers are the most threatening, assaultive, and harassing stalkers, particularly for women, this study shows that a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
(109 reference statements)
0
12
0
Order By: Relevance
“…Although the lower rate of female stalking contributes to the lack of knowledge of this phenomenon, there are broad social factors which influence the perception of women as stalkers. These social factors include gender-socialization scripts, which regard women as less dangerous and men as more capable of defending themselves, men being less likely to self-identify as victims of crime or report crime, men not receiving adequate victim support, and men being less likely to feel or admit fear for their safety (which is often a necessary component to stalking definitions; Langhinrichsen-Rohling, 2012; Logan, 2020b; Mullen et al, 2009; Scott et al, 2015; Wigman, 2009). Female victims of female-perpetrated stalking often have their sexuality questioned, as same-gender stalking is often incorrectly assumed to involve a homosexual relationship (Meloy et al, 2011; Stefanska et al, 2021).…”
Section: Behavior and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the lower rate of female stalking contributes to the lack of knowledge of this phenomenon, there are broad social factors which influence the perception of women as stalkers. These social factors include gender-socialization scripts, which regard women as less dangerous and men as more capable of defending themselves, men being less likely to self-identify as victims of crime or report crime, men not receiving adequate victim support, and men being less likely to feel or admit fear for their safety (which is often a necessary component to stalking definitions; Langhinrichsen-Rohling, 2012; Logan, 2020b; Mullen et al, 2009; Scott et al, 2015; Wigman, 2009). Female victims of female-perpetrated stalking often have their sexuality questioned, as same-gender stalking is often incorrectly assumed to involve a homosexual relationship (Meloy et al, 2011; Stefanska et al, 2021).…”
Section: Behavior and Motivationmentioning
confidence: 99%
“…Within community samples, Scott et al (2015) found that the victim was perceived to experience more distress and fear when the victim was female identified or the perpetrator was a male, with these perceptions stronger among female participants than male participants. Female victims of stalking showed higher levels of stalking-related fear and belief that the perpetrator could harm them (regardless of whether the perpetrator was male or female), whereas male victims of female stalking were significantly less concerned about being harmed (Logan, 2020b). Moreover, Sheridan and Scott (2010) found that violence among female stalkers was considered less dangerous than male-stalker-perpetrated violence.…”
Section: Behavior and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Stalking is associated with greater fixation and persistence, and is more likely to impact the target’s everyday life. Studies have consistently demonstrated the negative psycho-social effects of stalking victimization (Korkodeilou, 2017; Logan, 2020). These include everyday life changes such as routine deviation, job loss, reduced socialization and, for some, relocation.…”
mentioning
confidence: 99%